Optimization of high oleic palm oil-based trimethylolpropane esters synthesis in pulsed loop reactor - Abd Hamid, Hamidah (2016)
Some concerns about undesired saponification have been raised during the synthesis of high oleic palm oil-based trimethylolpropane (TMP) esters through transesterification of high oleic palm oil-based methyl esters (PME) with TMP in the presence of sodium methoxide catalyst by using a batch reflux reactor. A pulsed loop reactor was proposed to intensify the transesterification process. The main goal of this research work was to minimize fatty soap formation while maintaining the quality of high oleic TMP esters as biolubricant base oil by the use of a pulsed loop reactor. Response surface methodology (RSM) was applied to optimize the process conditions in the conventional reactor, based on maximum yield of high oleic TMP triesters (TMPTE) and minimum fatty soap amount. An Aspen Plus simulation study was conducted to facilitate the design of the proposed reactor. The performance of the pulsed loop reactor was evaluated under different process conditions to find the optimum yield of high oleic TMPTE and fatty soap. Subsequently, the quality of physicochemical properties of fractionated high oleic TMP esters were evaluated against other high oleic TMP esters base oils produced in the previous studies. The optimization study for the synthesis of high oleic TMP esters in the batch reflux reactor by using RSM has shown that the optimum yield of high oleic TMPTE and fatty soap were at 80 wt% and 85 mg/g respectively. The optimum process conditions were obtained at 130 °C, 0.3 wt% sodium methoxide catalyst and 53 min of reaction time, at fixed molar ratio of high oleic PME: TMP at 3.9:1 and vacuum level of 20 mbar. The total liquid and vapor product throughputs from Aspen Plus simulation were estimated at 2106 g/h and 192 g/h respectively under the optimum process conditions. The predicted heat duty values for the reactor and vacuum condenser was 0.25 kW and -0.01 kW respectively. After several commissioning runs, the newly designed pulsed loop reactor was successfully commissioned to produce more than 90 wt% of TMPTE in 1 hour. For the optimization of high oleic TMP esters synthesis in the pulsed loop reactor, the optimum process conditions were at 20 mbar, 1.0 wt% catalyst solution (30 % pure sodium methoxide in methanol), molar ratio of high oleic PME:TMP at 3.9: 1, 120 °C and 180 rpm. The optimum yield of high oleic TMPTE and fatty soap were 97 wt% and 167 mg/g, respectively. The predicted fatty soap amount from Aspen Plus simulation was 17 mg/g. The experimental fatty soap contains not only fatty soap but other substances such as TMP esters, PME, TMP and also the catalyst. The fractionated high oleic TMP esters satisfied ISO VG 46 lubricant standard and showed comparable properties to the other high oleic TMP esters base oils synthesized previously via conventional method.